Gold and Bitcoin Price Dynamics as a Reflection of Investor Sentiment - Nataliya Sheludʹko; Oleg Vasiurenko; Vyacheslav Lyashenko; Nadiia Morozova (Journal La Bisecoman, 2020)
The modern pandemic affects all areas of human activity. In this regard, various aspects of the preservation of economic activity become fundamental. One of these issues is the choice of an investment strategy, the choice of investment instruments. To do this, we examined the mutual dynamics of gold and bitcoin prices during the pandemic. For the analysis, we use the wavelet coherence methodology. This made it possible to substantiate some strategies and the choice of investment instruments.